Urgensi Pendidikan Pemakai (User Education) Bagi Pemustaka di Perpustakaan Perguruan Tinggi Agama Islam: Sebuah Konsep Penerapan Kampus Peradaban di UIN Alauddin Makassar - Almah, Hildawati (Jurnal Ilmu Perpustakaan & Informasi KHIZANAH AL-HIKMAH, 2014)
User education activities are expected to be held in any type of library, especially at the college library (including UIN and IAIN). Due to the presence of user education teaching can improve the function of libraries and librarians in supporting programs of Tri Dharma University institution. On the other hand, the basic for the importance of library user education is also intended for library users and the entire academic community (especially new students) to prepare them to be able to explore their skill in the necessary resources and use them for education. The ability to search and to access to this information will be very useful for students to develop a career of life inside and outside the campus then. Library and their existences especially in higher education institutions to university of Islam is a civilization buffer, the library is a place of pluralities of complex thinking of the dialectical process of creative thinkers who read the reality of plural. To answer the challenges of the constantly changing life, the land will be fertile earth to foster plurality, if the library maintained its role in education is to educate the nation and as a pillar of civilization that honors independent thinking.